Impact of Glycemic Control on Amsler Grid Findings in Patients with Diabetic Retinopathy in Palembang, Indonesia - Ramzi Amin; Ayu Aliyah (HM Publisher, 2025)
Background: Diabetic retinopathy (DR) remains a principal cause of vision impairment globally, frequently affecting the macula and central vision. This study aimed to investigate the association between glycemic control status and the presence of Amsler grid abnormalities in patients diagnosed with diabetic retinopathy in Palembang. Methods: This cross-sectional study was conducted at the outpatient ophthalmology and internal medicine clinics of a tertiary referral hospital in Palembang between January 2023 and December 2024. Patients aged 18 years or older with a confirmed diagnosis of type 1 or type 2 diabetes mellitus and any stage of diabetic retinopathy, capable of performing Amsler grid testing, were included after providing informed consent. Patients with other significant ocular pathologies affecting the macula or media opacities precluding fundus examination were excluded. Data collected included demographics, diabetes history, comprehensive ophthalmic examination findings, standardized Amsler grid testing results, and recent HbA1c levels. Glycemic control was categorized as good (<7.0%), fair (7.0-9.0%), and poor (>9.0%). Statistical analysis involved descriptive statistics, chi-square tests, t-tests/Mann-Whitney U tests, and multivariable logistic regression to assess the association between HbA1c levels and abnormal Amsler grid findings, adjusting for potential confounders. Results: A total of 385 patients with DR (mean age 58.2 ± 9.5 years; 53.8% female) were included. The mean duration of diabetes was 12.4 ± 6.8 years, and the mean HbA1c was 8.9% ± 2.1%. Abnormal Amsler grid findings were reported by 161 participants (41.8%). Patients with abnormal Amsler grid findings had significantly higher mean HbA1c levels compared to those with normal findings (9.8% ± 1.9% vs. 8.3% ± 1.8%, p < 0.001). In the multivariable logistic regression analysis, after adjusting for age, diabetes duration, DR severity, and hypertension, poor glycemic control (HbA1c >9.0%) was independently associated with significantly higher odds of having abnormal Amsler grid findings compared to good glycemic control (HbA1c <7.0%) (Adjusted Odds Ratio [aOR] = 3.45, 95% CI: 1.98-6.01, p < 0.001). Fair glycemic control (HbA1c 7.0-9.0%) also showed increased odds, although to a lesser extent (aOR = 1.82, 95% CI: 1.05-3.15, p = 0.032). Each 1% increase in HbA1c was associated with a 35% increased odds of abnormal Amsler findings. Conclusion: This study demonstrated a significant association between poorer glycemic control, as indicated by higher HbA1c levels, and the presence of abnormal Amsler grid findings among diabetic retinopathy patients in Palembang. These findings underscore the critical role of meticulous glycemic management in preserving not only retinal structure but also central visual function detectable through simple psychophysical tests. The Amsler grid serves as a valuable, accessible tool for functional monitoring in this patient population.